2012
DOI: 10.3390/ijerph9051810
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Common Mental Disorders in a Rural District of Kenya, and Socio-Demographic Risk Factors

Abstract: Association between common mental disorders (CMDs), equity, poverty and socio-economic functioning are relatively well explored in high income countries, but there have been fewer studies in low and middle income countries, despite the considerable burden posed by mental disorders, especially in Africa, and their potential impact on development. This paper reports a population-based epidemiological survey of a rural area in Kenya. A random sample of 2% of all adults living in private households in Maseno, Kisu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
73
11
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(114 citation statements)
references
References 31 publications
27
73
11
2
Order By: Relevance
“…The higher prevalence among women could be explained by considerable level of stress and suffering faced by women due to heavier burden of social and household responsibilities. In the current study the prevalence of common mental disorders was higher in older age group which was supported by similar community based studies from Ethiopia and Kenya [9,13]. In the current study being married was independently associated as a protective factor from common mental disorders which was similar with a study finding from a general population survey in Greece [6].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The higher prevalence among women could be explained by considerable level of stress and suffering faced by women due to heavier burden of social and household responsibilities. In the current study the prevalence of common mental disorders was higher in older age group which was supported by similar community based studies from Ethiopia and Kenya [9,13]. In the current study being married was independently associated as a protective factor from common mental disorders which was similar with a study finding from a general population survey in Greece [6].…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of the current study was found to be higher from similar community based studies in Kenya where the prevalence of common mental disorders was 10.8% and in Ethiopia, Butajira (17%). The reasons could be the Clinical Interview Schedule-Revised (CIS-R) was used in Kenyan study and the Butajira study used a cut-off point of ≥11 of the SRQ-20 items which makes the prevalence of common mental disorders lower [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding of more female patients agrees with the higher frequency of female patients found in a Kenyan studies [12,25]. The study reaffirms the findings from other studies about the predominance of female patients.…”
Section: Socio-demographic Characteristicssupporting
confidence: 91%
“…According to the United States government, Morocco has inadequate numbers of physicians (0.5 per 1,000 people) and in Ethopia, the physician to population ratio was 1:48,000 [39]. It in Kenya that a lesser psychiatrist to patient ratio was found with a physician to population ratio there is only 1 psychiatrist per 500,000 populations [25]. This may be because Nigeria is a more endowed country than Kenya, with more abundant human and material resources.…”
Section: Physician (Psychiatrist) To Patient and Psychiatrist To Popumentioning
confidence: 99%